2020
DOI: 10.1039/d0ma00692k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of precursor structure on porous carbons produced by iron-catalyzed graphitization of biomass

Abstract: This paper reports a systematic study into the effect of different biomass-derived precursors on the structure and porosity of carbons prepared via catalytic graphitization. Glucose, starch and cellulose are combined...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…137,138 Another study compared the graphitization of cellulose, starch and glucose, using iron nitrate as the iron precursor. 108 Cellulose and starch are both composed of polymers that are based on glucose monomers but while glucose is fully water-soluble, cellulose is insoluble and starch only swells to form gels. Pyrolysis of each of these precursors with aqueous iron nitrate resulted in carbons with very different structures, where cellulose and glucose carbons were mesoporous and the starch carbon was primarily microporous and with a much broader graphite XRD peak.…”
Section: Biopolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…137,138 Another study compared the graphitization of cellulose, starch and glucose, using iron nitrate as the iron precursor. 108 Cellulose and starch are both composed of polymers that are based on glucose monomers but while glucose is fully water-soluble, cellulose is insoluble and starch only swells to form gels. Pyrolysis of each of these precursors with aqueous iron nitrate resulted in carbons with very different structures, where cellulose and glucose carbons were mesoporous and the starch carbon was primarily microporous and with a much broader graphite XRD peak.…”
Section: Biopolymersmentioning
confidence: 99%
“…The few systematic studies that do exist have shown that it is possible to achieve dramatic variations in carbon structure through simple changes in precursors. 65,108 Another challenge in iron-catalyzed graphitization is understanding the mechanism. It is still not clear why some organic precursors produce graphitic shells while others generate graphitic nanotubes.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Various transition metals, including nickel, cobalt and iron, have been used to produce porous graphitic carbons [5], but iron is particularly attractive due to its high abundance and low toxicity. Aqueous iron salts such as iron nitrate and iron chloride have been used to produce graphitic carbon materials from a wide range of organic precursors, including small molecules such as glucose [6,7], synthetic [8] and natural polymeric species [9] and raw biomass such as sawdust [10][11][12]. During pyrolysis, the organic precursor decomposes to amorphous carbon and the iron precursor forms Fe or Fe 3 C nanoparticles which are believed to catalyse the conversion of amorphous carbon to graphitic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Other precursors produce highly disordered nanotubes, where the Fe 3 C/Fe catalyst has been observed to ‘burrow’ through the amorphous carbon, leaving a graphitic nanotube behind [ 15 ]. The driving force for graphitization and the reason for such varied structures being produced is not yet understood although it is believed to be in part driven by structural and compositional differences in the precursors [ 7 ]. Lignocellulosic biomass takes many forms and compositions, depending on the plant species and the part of the plant, e.g.…”
Section: Introductionmentioning
confidence: 99%